Terapia comunitária: ética, resiliência e aconselhamento pastoral - Silva, Elizabeth Luiza da (2014)
The area of Social Assistance has been experiencing a progress towards a closer relationship with the assumptions of the Social Assistance System (SUAS). One of the possibilities for the progress may be the Community Therapy (TC), which functions as a tool to assist in the care of others. This research investigates the transformations, from various community therapy circles, that we promoted along with these people from the Bolsa Família Program. These people come daily to the CRAS/CREAS Gama, Administrative City of Brasilia, searching for a better understanding of themselves and others, believing in the potential of transformation of each person. Community Therapy has interacted with Ethics, Resilience and Pastoral Counseling, proposals that help them improve and change their self-esteem, transforming people's daily lives. The community bond, the friendship and the presence of resilience make a reconstruction of lost links possible. Some of such transformation we have achieved with our work. We hope that this study encourages further investigations.